Regional and global conservation assessments for 200 vascular plant species from Costa Rica and Panama - Rodriguez, A.; Monro, A. K.; Chacon, O.; Solano, D.; Santamaria, D.; Zamora, N.; Gonzalez, F.; Correa, M. (Phytotaxa, 2011)
We present 200 species conservation assessments covering Costa Rica and Panama. Fifty-two of these represent global conservation assessments and 148 regional conservation assessments. Species were selected on the basis that they were present in the La Amistad Biosphere Reserve and deemed to be Keystone species for the reserve. We include basic taxonomic information, local names, uses, maps of the Extension of Occurrence and Area of Occupancy together with a discussion of the threats for each of the species assessed.